Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
D.
[tex]m(x) = 0 \\ - 3x = 0 \\ x = 0[/tex]
E.
[tex]m(x) = \frac{ - 3}{25} [/tex]
[tex] \frac{ - 3x}{x {}^{2} + 2x - 24} = \frac{ - 3}{25} [/tex]
[tex] - 3(x {}^{2} + 2x - 24) = - 3(x)(25) \\ divide \: both \: sides \: by - 3[/tex]
[tex]x {}^{2} + 2x - 24 = 25x[/tex]
[tex]x {}^{2} - 23x - 24 = 0[/tex]
[tex](x - 24)(x + 1) = 0 [/tex]
[tex]x = 24 \\ x = - 1[/tex]
Answer:
D
x=0
Step-by-step explanation:
E)
[tex]\frac{-3x}{x^2+2x-24} =\frac{-3}{25} \\x^2+2x-24=25x\\x^2+2x-25x-24=0\\x^2-23 x-24=0\\x^2-24x+x-24=0\\x(x-24)+1(x-24)=0\\(x-24)(x+1)=0\\x=24,-1[/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.